MSS-1 ～ MSS-2 (The Japanese Journal of SURGICAL METABOLISM and NUTRITION, 2017)
INTRODUCTION: Multidirectional sports introduce unique forces to the tibia that potentially induce more symmetrical distribution of bone mass and lower bone stress injury risk, when compared to unidirectional sports. PURPOSE: To compare tibial shaft size, shape, and estimated strength among competitive male and female athletes in sports with different loading demands. METHODS: High-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the tibial diaphysis (30% site) were performed in 149 NCAA Division I male and female cross-country and basketball athletes, female gymnastics and lacrosse athletes, and male American football athletes playing the wide receiver position. Tibial shaft outcomes relating to bone shape (ratio of the maximum and minimum moments of area [Imax/Imin]), size, and strength were compared by sport within each sex. Bone size outcomes were scaled to bone length to adjust for allometry. Kruskal-Wallis tests estimated group differences. RESULTS: In female athletes, gymnastics had a 13.5% lower Imax/Imin than cross-country (median [IQR] = 1.7 [1.4, 1.9] vs. 2.0 [1.8, 2.2], p=0.041) indicating a more symmetrical distribution of bone. In male athletes, football had the lowest Imax/Imin of all sports evaluated (median [IQR] = 1.6 [1.4, 1.8]), although this did not reach significance (p=0.051). There were no differences in tibial shaft outcomes between female gymnastics athletes or male football athletes and sex-matched basketball athletes (p>0.196). There were also no differences between female lacrosse and cross-country athletes (p>0.500). CONCLUSIONS: The contributions of multidirectional sports on tibial shaft characteristics are nuanced, and high-impact loading may be necessary to develop a more symmetrical shape, which may influence tibial bone stress injury risk.